Analisis Penerimaan Pengguna E-Filing Menggunakan Model Unified Theory Acceptance and Use of Technology (UTAUT) - Arfah Habib Saragih; Nadhirotul Ulfa Septamia (Jurnal Kajian Akuntansi, 2019)
E-filing is form of modern tax administration as one of the way to improve community service using the improvement of technologies. E-filing has purposes to give an easy service for individual taxpayer submitting tax return and also to improve the individual taxpayer compliance to report Individual Annual Income Tax Returns. However, e-filing is not used by all individual taxpayers yet. It is shown by the decrease number of compliance level of Annual Income Tax Return report. This research is to acknowledge user acceptance of e-filing using Unified Theory Acceptance and Use of Technology (UTAUT) Model. Research method is using an descriptive quantitative approach with a purposive sampling technique. The sample was used 150 respondents with a survey using a questionnaire. The significant results is shown by the effect of performance expectancy to behavioral intention and behavioral intention to use behavioral. The weak effects is shown by the correlation berween effort expectancy to behavioral intention.Keywords: E-Filing; Individual Tax Retur; Individual Taxpayer; UTAUT